Pengaruh Intelectual Capital, Financing To Deposit Ratio, Dan Fee Based Income Terhadap Earning Per Share Pada Bank Umum Syariah Di Indonesia - Siregar, Elisa Meria Sari; Silalahi, Alisraja Dison (UNIVERSITAS DHARMAWANGSA, 2023)
This research aims to determine the influence of Intellectual Capital, Financing to Deposit Ratio and Fee Based Income on EarningPer Share in Sharia Commercial Banks in Indonesia for the 2019-2021 period. The independent variables in this research are Intellectual Capital, Financing to Deposit Ratio and Fee Based Income. The dependent variable in this research is Earning Per Share. The research sample is a Sharia Commercial Bank (BUS) in Indonesia which is registered with the Financial Services Authority (OJK) in 2019-2021. The sample was selected using a purposive sampling technique to obtain seven Sharia Commercial Banks. This research uses multiple linear regression analysis research methods. The research results show that intellectual capital (IC) influences Earning Per Share both partially. This shows that good IC management in Islamic banks has an effect on Earning Per Share of Islamic banks. The research results show that the Financing to Deposit Ratio variable and the Fee based income variable have no effect on Earning Per Share either partially or simultaneously.Keywords: Intellectual Capital, Financing to Deposit Ratio, Fee Based Income, Earning Per Share